Three essays on financial economics - Alhaj-Yaseen, Yaseen Salah (Kansas State University, 2010)
For a unique sample of Israeli stocks that went public in the U.S. and then cross-listed in the home market, Tel Aviv Stock Exchange (TASE), this dissertation consists of three essays examining the dynamics of return spillovers and volume-return interactions across markets and the valuation effect around the event of cross-listing and delisting from the home market. In Chapter II, I investigate the role of trading volume in the information flow and return spillovers between the U.S. and Israeli markets. Findings suggest that the dynamics of volume-return interactions across markets can provide us with valuable information regarding future price movements, which can be a useful tool to predict future returns. I also find the home market to dominate the host market in pricing these stocks, which is consistent with the Home Bias hypothesis. In Chapter III, I analyze the impact of the event of cross-listing on stock returns and risk exposure. The behavior of abnormal returns around the cross-listing date implies that cross-listing in TASE is an effective mechanism in reducing market segmentation between the U.S. and the Israeli capital markets. Risk assessment following the cross-listing suggests a decline firms’ overall risk exposure, indicating a higher degree of integration between the two markets due to cross-listing. In Chapter IV, I evaluate changes in the cost-of-capital for Israeli firms after delisting voluntary from TASE, the home market, while maintaining their listing in the U.S., the host market. The results show a significant positive shift in U.S. and negative shift in Israeli market risk exposure after the delisting. These results indicate that firms delisting form their home market (TASE), face greater risk exposure, higher required returns on their stocks and, hence, higher cost-of-capital after delisting.
Keywords: Cross Listing; International Listing; Return Spillover; Trading Volume; Information Flow; International Delisting; Economics, Finance (0508)